Radiotherapy for neovascular age-related macular degeneration. - Evans, JR; Sivagnanavel, V; Chong, V (2010)
BACKGROUND: Radiotherapy has been proposed as a treatment to prevent new vessel growth in people with neovascular age-related macular degeneration (AMD). OBJECTIVES: The aim of this review was to examine the effects of radiotherapy on neovascular AMD. SEARCH STRATEGY: We searched the Cochrane Central Register of Controlled Trials (CENTRAL) (which contains the Cochrane Eyes and Vision Group Trials Register) in The Cochrane Library Issue 3, 2010, MEDLINE (January 1950 to March 2010), EMBASE (January 1980 to March 2010), Latin American and Caribbean Health Sciences Literature Database (LILACS) (January 1982 to March 2010), the metaRegister of Controlled Trials (mRCT) (www.controlled-trials.com) (March 2010) and ClinicalTrials.gov (http://clinicaltrials.gov) (March 2010). There were no language or date restrictions in the search for trials. The electronic databases were last searched on 23 March 2010. We also wrote to investigators of trials included in the review to ask if they were aware of any other studies. SELECTION CRITERIA: We included all randomised controlled trials in which radiotherapy was compared to another treatment, sham treatment, low dosage irradiation or no treatment in people with choroidal neovascularisation secondary to AMD. DATA COLLECTION AND ANALYSIS: Two review authors independently extracted the data. We combined relative risks using a random-effects model. We estimated the percentage of the variability in effect estimates that was due to heterogeneity, rather than sampling error, using I(2). MAIN RESULTS: Thirteen trials (n=1154) investigated external beam radiotherapy with dosages ranging from 7.5 to 24 Gy; one additional trial (n=88) used plaque brachytherapy (15Gy at 1.75mm for 54 minutes/12.6 Gy at 4mm for 11 minutes). Most studies found effects (not always significant) that favoured treatment. Overall there was a small statistically significant reduction in risk of visual acuity loss in the treatment group. There was considerable inconsistency between trials and the trials were considered to be at risk of bias, in particular because of the lack of masking of treatment group. Subgroup analyses did not reveal any significant interactions, however, there were small numbers of trials in each subgroup (range three to five). There was some indication that trials with no sham irradiation in the control group reported a greater effect of treatment. The incidence of adverse events was low in all trials; there were no reported cases of radiation retinopathy, optic neuropathy or malignancy. Three trials found non-significant higher rates of cataract progression in the treatment group. AUTHORS' CONCLUSIONS: This review currently does not provide convincing evidence that radiotherapy is an effective treatment for neovascular AMD. If further trials are to be considered to evaluate radiotherapy in AMD then adequate masking of the control group must be considered.